What is 9/6 minus 6/7?
Looking for the result of 9/6 - 6/7? Follow this step-by-step guide to understand how to subtract these two fractions.
How to subtract 9/6 by 6/7?
- Multiply the numerator of the first term, with the denominator of the second term: 9 × 7 = 63
- Multiply the numerator of the second term, with the denominator of the first term: 6 × 6 = 36
- Subtract both of these results together to form the new numerator: 63 − 36 = 27
- Multiply both denominators together to form the new denominator: 6 × 7 = 42
- Combine the results to get the new fraction: 27/42
- Simplify the fraction (27/42) by dividing both the numerator and the denominator by their GCD (3):
- 27/3 = 9
- 42/3 = 14
- This gives: 9/14.
The result of subtracting 9/6 and 6/7 is : 9/14 (or 0.64285714285714 in its decimal form)